PKM PEMBERDAYAAN IBU-IBU PKK DALAM PENGOLAHAN LIMBAH RUMAH TANGGA MENJADI BERNILAI EKONOMI DAN PEMASARANNYA MELALUI MEDIA ONLINE DI DESA ADAT BUALU BALI - Yamawati, Ni Kd Sioaji; Dewi, I Gusti Ayu Ratih Permata; Pertama, I Gde Agung Wira (JURNAL SEWAKA BHAKTI, 2025)
Waste has numerous impacts on humans and the surrounding environment. Waste is a challenging problem to address in both large and small cities in Indonesia, including in the Bualu Traditional Village, Badung. This is due to the community's consumer habits, which consistently produce waste, especially plastic, with every product used. Creatively utilizing plastic waste for handicrafts is a viable solution for transforming plastic waste into useful items, even those with sales value and aesthetic appeal. The series of training sessions provided to PKK (Family Welfare Movement) women has positively impacted participants' knowledge, skills, and confidence in managing household waste into creative, marketable products. Participants are not only able to create high-quality recycled products, but also understand how to set appropriate selling prices and market products through digital platforms.